Giant fibroadenoma - Beltrán Guañarita, Jorge; Méndez, Arturo; Laviña, Raúl; Delgado, Fernando (Cirugía del Uruguay, 1990)
Giant fibroadenoma is a difficult clinical and paraclinical diagnosis of breast dysplasia.